Online Sex Partner Meeting Venues as a Risk Factor for Testing HIV Positive Among a Community-Based Sample of Black Men Who Have Sex With Men. Issue 6 (June 2016) - Eaton, Lisa A.; Maksut, Jessica L.; Gamarel, Kristi E.; Siembida, Elizabeth J.; Driffin, Daniel D.; Baldwin, Robert
Abstract : Objectives: In the United States, black men who have sex with men (BMSM) are disproportionately affected by the HIV epidemic. The elevated estimates of HIV among BMSM suggest that to slow rates of HIV infections, a range of factors that may contribute to transmission must be researched. Use of online venues for seeking out sex partners is one such area that may further advance our understanding of risks for HIV among BMSM. Methods: Black men who have sex with men residing in Atlanta, GA, reporting HIV-negative/unknown status completed survey assessments and HIV antibody testing. Logistic regression using generalized linear modeling was used to conduct both bivariate and multivariable analyses of psychosocial variables—that is, substance use, sexually transmitted infection symptoms/diagnoses, sexual risk behavior, online sex partner meeting, and HIV test results. Results: Two hundred thirty-two BMSM tested HIV negative and 39 BMSM tested HIV positive (14% new diagnoses). Reporting symptoms of a rectal sexually transmitted infection (odds ratio, 4.28; 95% confidence interval, 1.06–15.41) and use of sexual networking apps (odds ratio, 2.15; 95% confidence interval, 1.06–4.36) were both associated with testing HIV positive in a multivariable analysis. Conclusions: The use of sexual networking apps is associated with risks for HIV infection above and beyond what is captured by sexual risk behavior alone. Evaluating how sexual networking apps affect sexual networks and social norms regarding sexual risk taking and HIV transmission is an important and novel area for HIV prevention and intervention development.